Biochemical, Molecular, and Clinical Characterization of Patients With Primary Carnitine Deficiency via Large-Scale Newborn Screening in Xuzhou Area - Zhou, Wei; Li, Huizhong; Huang, Ting; Zhang, Yan; Wang, Chuanxia; Gu, Maosheng (Frontiers in Pediatrics, 2019)
Background: Primary carnitine deficiency (PCD) is attributed to a variation in the SLC22A5 (OCTN2) gene which encodes the key protein of the carnitine cycle, the OCTN2 carnitine transporter. PCD is typically identified in childhood by either hypoketotic hypoglycemia, or skeletal and cardiac myopathy. The aim of this study was to the clinical, biochemical and molecular characteristics of PCD patients via newborn screening with tandem mass spectrometry (MS/MS). Methods: MS/MS was performed to screen newborns for inherited metabolic diseases. SLC22A5 gene mutations were detected in the individual and/or their family member by DNA mass array and next-generation sequencing (NGS). Results: Among the 236,368 newborns tested, ten exhibited PCD, and six others were diagnosed with low carnitine levels caused by their mothers, who had asymptomatic PCD. The incidence of PCD in the Xuzhou area is approximately 1:23,637. The mean initial free carnitine (C0) concentration of patients was 6.41± 2.01 μmol/L, and the follow-up screening concentration was 5.80 ± 1.29 μmol/L. After treatment, the concentration increased to 22.8 ± 4.13 μmol/L. Conclusion: This study demonstrates the important clinical value of combining MS/MS and NGS for the diagnosis of PCD and provides new insight into the diagnosis of PCD and maternal patients with PCD using C0 concentration and SLC22A5 mutations.